2018
DOI: 10.1016/j.fct.2018.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid co-administered with rosuvastatin reduces reproductive impairment in the male offspring from male rats exposed to the statin at pre-puberty

Abstract: Obesity during childhood and adolescence is closely related to dysfunctions on lipid profile in children. Rosuvastatin is a statin that decreases serum total cholesterol. Ascorbic acid is an important antioxidant compound for male reproduction. Pre-pubertal male rats were distributed into six experimental groups that received saline solution 0.9% (vehicle), 3 or 10 mg/kg/day of rosuvastatin, 150 mg/day of ascorbic acid, or 3 or 10 mg/kg/day of rosuvastatin co-administered with 150 mg/day of ascorbic acid by ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Ascorbate, an intracellular form of ascorbic acid, regulates DNA demethylation and histone demethylation (Young, Zuchner, and Wang 2015), thus presenting an important epigenetic role. Leite et al (2018) found that paternal supplementation with AA ameliorated the reproductive damage in the male offspring attributed to rosuvastatin, probably due to AA action on inhibition of genetic and epigenetic changes in paternal spermatozoa.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Ascorbate, an intracellular form of ascorbic acid, regulates DNA demethylation and histone demethylation (Young, Zuchner, and Wang 2015), thus presenting an important epigenetic role. Leite et al (2018) found that paternal supplementation with AA ameliorated the reproductive damage in the male offspring attributed to rosuvastatin, probably due to AA action on inhibition of genetic and epigenetic changes in paternal spermatozoa.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies suggested epigenetic changes were attributed to statin exposure (Bustan and Jawad 2017;Leite et al 2018). Bustan and Jawad (2017) associated paternal or maternal exposure to atorvastatin or rosuvastatin with alterations in fertility in their offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Inconsistent data exist for rosuvastatin on this context. [21][22][23] Interestingly, transient azoospermia has been reported in a male patient with oligoasthenozoospermia after rosuvastatin administration. Spermatozoa reappeared in the ejaculated semen at two weeks after drug withdrawal and increased to baseline levels at 16 weeks.…”
Section: Reprodumentioning
confidence: 97%
“…[15][16][17] Previous studies found that SARS, 1 of the 3 epidemic coronaviruses to emerge in the past 20 years and that shows similar clinical presentations to COVID-19, 18 could cause orchitis 19 and focal testicular atrophy. 20 Considering the tens of millions of COVID-19 cases and that men are more vulnerable to COVID-19 than women, [21][22][23] it is imperative to determine the effect of COVID-19 on male reproduction. 24 Several studies have been performed on this topic.…”
Section: Introductionmentioning
confidence: 99%